Counting the poor new thinking about European poverty measures and lessons for the United States - Besharov, Douglas J.; Couch, Kenneth A. (Kenneth Alan) (New York ; Oxford : Oxford University Press, 2012)
With contributions from the world's foremost authorities on social measurement, this volume promises to be the definitive reference for poverty researchers and policymakers seeking to disengage politics from measurement.
Description based on online resource; title from PDF title page (viewed on July 16, 2012).
Includes bibliographical references and index.
Keywords: Poverty -- European Union countries; Poverty -- United States